Too Lucky to Be a Victim?: an Exploratory Study of Online Harassment and Hate Messages Faced by Social Media Influencers - Valenzuela-García, Noelia (European journal on criminal policy and research, 2023)
Influencers are persistently exposed through social media. Once almost unapproachable, celebrities are now open to daily interaction with the public. From comments, polls, emails, and even private messages, the public can engage with their celebrities with a mere click. While this engagement provides influencers with advantages, it also renders them particularly susceptible to online harassment and toxic critics. This paper investigates the characteristics, impact, and reactions to cyber victimisation among social media influencers. To accomplish this objective, the paper presents the findings of two studies: a self-reported online victimisation survey conducted among Spanish influencers and an online ethnography. The results indicate that over 70% of influencers have encountered some form of online harassment and toxic critics. Cyber victimisation, its effects, and reactions vary across socio-demographic characteristics and the influencers’ profiles. Furthermore, the qualitative analysis of the online ethnography reveals that harassed influencers can be classified as non-ideal victims. The implications of these findings for the literature are discussed.